Installation and Activation of Fiber To The Home (FTTH) Network Using Gigabit Passive Optical Network (GPON) Technology and Quality of Service (QoS) Analysis - Ramadan, Zardi; Yulindon, Yulindon; Yustini, Yustini; Asril, Aprinal Adila (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
This research discusses the design, implementation, and evaluation of Fiber to the Home (FTTH) networks using Gigabit Passive Optical Network (GPON) technology, including network topology design, device installation, activation, and quality of service analysis. Attenuation measurements were conducted before and after activation to ensure compliance with ITU-T G.984 standards, while Quality of Service (QoS) analysis using Wireshark application evaluated parameters such as throughput, packet loss, delay, and jitter. Results show an increase in network efficiency after activation, with a decrease in attenuation. QoS measurements showed excellent network performance, with high throughput (2,595 Kbps), no packet loss, low delay (3.106 ms), and minimal jitter (3.128 ms). This study provides a comprehensive overview of FTTH network implementation and the importance of quality of service evaluation to ensure optimal performance for end users. The systematic approach used can be a valuable guide for telecom operators and internet service providers in implementing reliable and efficient FTTH networks. The study also emphasizes the importance of continuous monitoring and evaluation of network performance, contributing to the technical understanding of FTTH implementation and highlighting the implications for end-user experience as well as the potential for future broadband service development.